Library management for the digital age a new paradigm - Todaro, Julie 1950- (Rowman & Littlefield, 2014)
"This updated edition of the renowned library management textbook provides a comprehensive overview of the techniques needed to effectively manage a contemporary library or information center"--Provided by publisher.